2021
DOI: 10.33262/cienciadigital.v5i4.1865
|View full text |Cite
|
Sign up to set email alerts
|

Communicative language teaching approach in the development of speaking skill

Abstract: Introduction. Oral communication is perhaps the most important skill while learning a foreign language. The conventional English teaching method that is applied at the different educational levels based on grammar and writing, does not allow the development of the necessary communication skills. The communicative teaching of language has been the subject of this research, in which its effectiveness has been treated using different resources and skills. Objective. This research aims to apply communicative langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Here comes the role of the teacher to expose their students to more listening periods to correctly pronounce English. This finding coincides with the findings of other previous studies such as Guado & Mayorga, (2021). The results showed that the increase in speaking ability of the experimental group was greater than in the control group due to using communicative language teaching.…”
Section: Discussion and Interpretation Of The Resultssupporting
confidence: 92%
“…Here comes the role of the teacher to expose their students to more listening periods to correctly pronounce English. This finding coincides with the findings of other previous studies such as Guado & Mayorga, (2021). The results showed that the increase in speaking ability of the experimental group was greater than in the control group due to using communicative language teaching.…”
Section: Discussion and Interpretation Of The Resultssupporting
confidence: 92%
“…They can deal with simple and short conversations but it is necessary to improve their speaking through challenging activities supported with technology that is part of their Jorge Patricio Zhuño-Morocho; Martha Magdalena Guamán-Luna 108 daily lives. The communicative language teaching approach presents principles and objectives that permit the learning process of a language to use classroom activities like dialogues, role-plays, and information-gap activities, based on group work and task work, had been effective to help the progress of the speaking skill (Oviedo & Mena, 2021). From table and figure 4, it was possible to show that most of the students say that in the English class the teacher sometimes uses social media to motivate them to practice their speaking skills (Singh, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to mention that rural education needs to implement active strategies to use technology and virtual education to improve communicative skills not only because the students are digital natives but also because it is a world surrounded by technology and electronic devices. These skills are essential because they allow learners to diffuse coherently and order oral information like arguments, feeling, opinions, or personal information according to the level, using the sub-skills language to function in a real context (Oviedo & Mena, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A fluent person may have already developed his/her communicative competence. In other words, this person will be able to use language without hesitation when having a conversation (Samifanni, 2020;Oviedo & Mena, 2021). Additionally, when a speaker is fluent, this person can use the language patterns appropriately.…”
Section: Fluencymentioning
confidence: 99%